Association of COVID-19 mortality with serum selenium, zinc and copper: Six observational studies across Europe - Demircan, Kamil; Chillon, Thilo Samson; Bracken, Tommy; Bulgarelli, Ilaria; Campi, Irene; Du Laing, Gijs; Fafi-Kremer, Samira; Fugazzola, Laura; Garcia, Alejandro Abner; Heller, Raban; Hughes, David J.; Ide, Louis; et al. (Frontiers in Immunology, 2022)
Certain trace elements are essential for life and affect immune system function, and their intake varies by region and population. Alterations in serum Se, Zn and Cu have been associated with COVID-19 mortality risk. We tested the hypothesis that a disease-specific decline occurs and correlates with mortality risk in different countries in Europe. Serum samples from 551 COVID-19 patients (including 87 nonsurvivors) who had participated in observational studies in Europe (Belgium, France, Germany, Ireland, Italy, and Poland) were analyzed for trace elements by total reflection X-ray fluorescence. A subset (n=2069) of the European EPIC study served as reference. Analyses were performed blinded to clinical data in one analytical laboratory. Median levels of Se and Zn were lower than in EPIC, except for Zn in Italy. Nonsurvivors consistently had lower Se and Zn concentrations than survivors and displayed an elevated Cu/Zn ratio. Restricted cubic spline regression models revealed an inverse nonlinear association between Se or Zn and death, and a positive association between Cu/Zn ratio and death. With respect to patient age and sex, Se showed the highest predictive value for death (AUC=0.816), compared with Zn (0.782) or Cu (0.769). The data support the potential relevance of a decrease in serum Se and Zn for survival in COVID-19 across Europe. The observational study design cannot account for residual confounding and reverse causation, but supports the need for intervention trials in COVID-19 patients with severe Se and Zn deficiency to test the potential benefit of correcting their deficits for survival and convalescence.